2002
DOI: 10.1161/hy02t2.102908
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Increases Intracellular NO Concentration via Ca 2+ Signaling in Inner Medullary Collecting Duct

Abstract: Abstract-The present study was designed to determine whether arginine vasopressin (AVP) stimulates NO production in the epithelial collecting duct cells of the inner medulla (IMCDs) and if this is mediated through Ca 2ϩ signaling. Thin tissue layers containing IMCDs were dissected from Sprague-Dawley rats. Intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) and NO production were measured in IMCDs by a fluorescence imaging system with the use of fura 2-AM and the cell-permeable form of the NO-sensitive dye 4,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…These observations were consistent with the direct observations that AVP stimulated NO production in the epithelial cells of inner medullary collecting ducts (IMCD) as determined by fluorescent microscopy (67) and other reports that AVP stimulated increases of urinary cGMP concentrations (103) and that the inhibition of NOS acutely enhanced systemic pressor responses to AVP (35,109).…”
Section: Acute Counterregulatory Action Of Renal Medullary No On Circsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations were consistent with the direct observations that AVP stimulated NO production in the epithelial cells of inner medullary collecting ducts (IMCD) as determined by fluorescent microscopy (67) and other reports that AVP stimulated increases of urinary cGMP concentrations (103) and that the inhibition of NOS acutely enhanced systemic pressor responses to AVP (35,109).…”
Section: Acute Counterregulatory Action Of Renal Medullary No On Circsupporting
confidence: 91%
“…These techniques were initially used to study mechanisms of AVP-stimulated NO production in the IMCD epithelial cells. It was shown that AVP produced a rapid increase of [Ca 2ϩ ] i followed by a significant increase of intracellular NO within these cells (67). The NO response was abolished both by an NO scavenger, carboxy 2-(4-carboxyphenyl)-4,4,5,5,tetramethylimidazoline-1-oxyl-3-oxide, and by preincubation with the Ca 2ϩ -ATPase inhibitor thapsigargin.…”
Section: Evidence For Paracrine and Autocrine No Function In The Renamentioning
confidence: 98%
“…Taylor et al 65 found that in ET B receptor-deficient rats, medullary NOS activity and renal endothelin production are decreased, indicating that renal endothelin regulates NOS 3 activity as reported for the thick ascending limb. 66 Mori et al 67 found that vasopressin stimulated a rapid increase in intracellular NO via increased intracellular calcium levels in the inner medullary collecting duct. Although they did not assess which NOS isoform was activated, NOS 3 is likely responsible because of its high expression in the collecting duct.…”
Section: Hormonal Regulation Of Nosmentioning
confidence: 99%
“…3,4 Left kidneys were removed and cleared of blood by perfusion with Hank's balanced salt solution (Life Technologies) with 20 mmol/L HEPES (HBSSH; adjusted to pH 7.4; Sigma) and 1 mg/mL bovine serum albumin. A latex-microsphere solution (2.7% wt/vol, 0.2-m diameter; Polysciences) was perfused in some rats to disrupt the endothelial cells of the VR 4 so that changes in pericyte free radicals could be measured.…”
Section: Tissue Fluorescence Imagingmentioning
confidence: 99%
“…3,4 We have demonstrated that NO serves as a paracrine substance that mediates cross-talk between the tubular epithelium of the medullary thick ascending limb (mTAL) and contractile VR pericytes. 4 It was shown that angiotensin II (AngII) could not directly increase intracellular NO levels in either endothelial cells or pericytes of the outer medullary VR.…”
mentioning
confidence: 99%